2013
DOI: 10.1371/journal.pone.0067734
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Sustained Virologic Response with Peginterferon Plus Ribavirin for Chronic Hepatitis C Virus Infection in HIV Infected Patients in Rio de Janeiro, Brazil

Abstract: BackgroundThe standard treatment for chronic hepatitis C virus (HCV) infection in HIV-infected subjects is the combination of alfapeginterferon (PEG-IFN) plus ribavirin. We designed this study to evaluate the rate of SVR and predictors of SVR in a public health setting in Rio de Janeiro, Brazil.MethodsRetrospective cohort study of HCV/HIV co-infected patients treated with PEG-IFN plus ribavirin from 2004 to 2011 in 3 outpatient units in Rio de Janeiro. Exposure variables included age, sex, CD4+ cell count, HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…[94] A study conducted in a public health setting in Brazil observed a similarly low SVR rate (27%) as those observed in clinical trials. [95] The use of weight-based ribavirin (compared to fixed low-doses of ribavirin) and extended duration of therapy has resulted in increased SVR rates, as demonstrated in the PRESCO trial in co-infected patients (SVR 50%) [96] In addition, avoidance of antiretroviral drugs such as zidovudine, didanosine, and stavudine in combination with ribavirin is recommended, given the risks of severe anaemia, pancreatitis, and lactic acidosis. [97-101]…”
Section: Management Of Hiv and Hcv Co-infectionmentioning
confidence: 99%
“…[94] A study conducted in a public health setting in Brazil observed a similarly low SVR rate (27%) as those observed in clinical trials. [95] The use of weight-based ribavirin (compared to fixed low-doses of ribavirin) and extended duration of therapy has resulted in increased SVR rates, as demonstrated in the PRESCO trial in co-infected patients (SVR 50%) [96] In addition, avoidance of antiretroviral drugs such as zidovudine, didanosine, and stavudine in combination with ribavirin is recommended, given the risks of severe anaemia, pancreatitis, and lactic acidosis. [97-101]…”
Section: Management Of Hiv and Hcv Co-infectionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) infection is highly prevalent (20-40%) in subjects infected with the human immunodeficiency virus (HIV) because of common transmission pathways [ 1 ]. HIV/HCV coinfected subjects have higher HCV viral load, faster progression to cirrhosis, higher incidence of liver decompensation and liver related deaths when compared to HCV monoinfected patients [ 2 , 3 ]. The primary goal of HCV therapy is to cure the infection, which results in the elimination of the virus after cessation of treatment in a variable proportion of patients according to genotype [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found no association between CD4 and HIV-RNA count and the SVR rate. This is a controversial finding in the literature, since some authors found no relationship between CD4 cell count [47,48] or HIV-RNA viral load and SVR. However, Pineda et al [27] observed that CD4 cell count above 300 cell/mm 3 was an independent factor of better SVR.…”
Section: Discussionmentioning
confidence: 93%